Veterinary Services suitable for Privatization in Sheep and Goat Farming - M.Srinivasa Reddy; B. Sudhakar Rao (Journal of Agricultural Extension Management, 2025)
Privatization of veterinary services is  considered as one of the strategies to improve the quality of the services and decrease the burden on scarce public resources . This paper attempts to identify the veterinary services suitable for privatization, in the areas of sheep and goat farming in Andhra Pradesh. The study concludes that veterinary services, which have economic importance need to be identified and methodologies evolved for their adoption by the farmers